Effective Synthesis of Highly Oxidized Graphene Oxide That Enables Wafer-scale Nanopatterning: Preformed Acidic Oxidizing Medium Approach - Chun-Hu Chen (Nature Portfolio, 2017)
Abstract Demand for rapid and massive-scale exfoliation of bulky graphite remains high in graphene commercialization and property manipulation. We report a procedure utilizing “preformed acidic oxidizing medium (PAOM)” as a modified version of the Hummers’ method for fast and reliable synthesis of graphene oxide. Pre-mixing of KMnO4 and concentrated H2SO4 prior to the addition of graphite flakes enables the formation of effectively and efficiently oxidized graphene oxide (EEGO) featured by its high yields and suspension homogeneity. PAOM expedites diffusion of the Mn-oxidants into the graphite galleries, resulting in the rapid graphite oxidation, capable of oxidizing bulky graphite flakes (~0.8 mm in diameter) that can not be realized by the Hummers’ method. In the scale-up tests, ten-time amount of graphite can be completely exfoliated by PAOM without need of extended reaction time. The remarkable suspension homogeneity of EEGO can be exploited to deposit ultra-flat coating for wafer-scale nanopatterning. We successfully fabricated GO optical gratings with well-defined periodicity (300 nm) and uniform thickness (variation <7 nm). The combination of the facile and potent PAOM approach with the wafer-scale patterning technique may realize the goal for massive throughput graphene nanoelectronics.